2021
DOI: 10.1007/s00253-021-11701-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficient production of immunologically active Shigella invasion plasmid antigens IpaB and IpaH using a cell-free expression system

Abstract: Shigella spp. invade the colonic epithelium and cause bacillary dysentery in humans. Individuals living in areas that lack access to clean water and sanitation are the most affected. Even though infection can be treated with antibiotics, Shigella antimicrobial drug resistance complicates clinical management. Despite decades of effort, there are no licensed vaccines to prevent shigellosis. The highly conserved invasion plasmid antigens (Ipa), which are components of the Shigella type III secretion system, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 71 publications
(127 reference statements)
0
7
0
Order By: Relevance
“…The immunogenicity and protective efficacy of VirGα were also investigated using a mucosal route and a clinically advanced mucosal adjuvant, the E. coli double mutant heat-labile toxin (dmLT). Mice were immunized IN with 2.5, 5, or 10 µg of VirGα admixed with dmLT on days 0, 14, and 28; this schedule was selected based on results from previous studies 19 , 45 . VirGα-specific serum IgG responses after the 1st and 2nd vaccinations were modest but increased dramatically after the 3rd immunization.…”
Section: Resultsmentioning
confidence: 99%
“…The immunogenicity and protective efficacy of VirGα were also investigated using a mucosal route and a clinically advanced mucosal adjuvant, the E. coli double mutant heat-labile toxin (dmLT). Mice were immunized IN with 2.5, 5, or 10 µg of VirGα admixed with dmLT on days 0, 14, and 28; this schedule was selected based on results from previous studies 19 , 45 . VirGα-specific serum IgG responses after the 1st and 2nd vaccinations were modest but increased dramatically after the 3rd immunization.…”
Section: Resultsmentioning
confidence: 99%
“…IpaB was produced using Vaxcyte’s proprietary Xpress + CFPS platform ( 22 ). The native protein sequence was used as a template to generate multiple IpaB single-site variants that efficiently incorporated nnAA p -azidophenylalanine (pAMF) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We report here for the first time the successful development of a Shigella OPS-conjugate vaccine that employs IpaB as a carrier antigen. IpaB is known to be potently immunogenic ( 17 , 18 , 22 , 26 ). IpaB-specific antibodies are present in high levels in sera from individuals living in areas of endemicity ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, the addition of LDAO during the purification process dramatically improved the recovery yields of nonaggregated antigens. 23 25 Since we are interested in utilizing these target antigens as carrier proteins for generating novel conjugate vaccines (CVs) using click chemistry, we wanted to further investigate the impact of LDAO on the copper-free SPAAC reaction.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that surfactants like sodium dodecyl sulfate (SDS), cetyltrimethylammonium bromide (CTAB), and sodium decanoate can have a meaningful impact on the kinetics of both copper-catalyzed and copper-free click chemistry reactions. In a recent study, Schneider et al showed that the addition of SDS and N -lauroylsarcosine (NLS) enhanced the rate of a copper-catalyzed SPAAC reaction, resulting in higher yields of conjugated materials, while elsewhere, the presence of certain surfactants at concentrations above the critical micelle concentration (CMC) in click chemistry reactions was found to improve both conjugation efficiency and reaction kinetics. , Recently, we also successfully utilized a zwitterionic detergent, lauryldimethylamine N -oxide (LDAO), to purify a protein vaccine antigen that showed high propensity for aggregation and precipitation by itself. Intriguingly, the addition of LDAO during the purification process dramatically improved the recovery yields of nonaggregated antigens. Since we are interested in utilizing these target antigens as carrier proteins for generating novel conjugate vaccines (CVs) using click chemistry, we wanted to further investigate the impact of LDAO on the copper-free SPAAC reaction.…”
Section: Introductionmentioning
confidence: 99%